Knowledge Networks, the Internet, and Development - Cukor, Peter; McKnight, Lee (Tufts Archival Research Center, 2005)
Volume 25, Issue 1. Winter Cukor and McKnight discuss how increased access and more affordable connectivity to advanced information and communication technologies, especially wireless and Internet services, are making on-line information increasingly available to development professionals and citizens of developing countries.